Workplace environment around physicians' burnout: A qualitative study in French hospitals - Jordan Sibeoni; Laura Bellon-Champel; Laurence Verneuil; Caroline Siaugues; Anne Revah-Levy; Olivier Farges (Nordic Association of Occupational Safety and Health (NOROSH), 2021)
OBJECTIVE: Burnout among physicians in public hospital has become a major public health issue in most Western countries. Qualitative literature has underlined the importance of interpersonal and group aspects in this context. Yet, no qualitative study has ever explicitly explored workplace direct environment's association with physicians' burnout. This study aimed to fill this gap. METHODS: This qualitative study used the five-stage inductive process to analyse the structure of lived experience (IPSE) approach and was conducted in French hospitals. We interviewed 45 participants - 16 with a lived experience of burnout and 29 of their colleagues - 19 women/26 men, (13 radiologists, 12 gastroenterologists, 10 gastrointestinal surgeons and 10 residents) from February 2018 to April 2019. Data analysis followed the IPSE analytic procedure and was conducted in two stages: three individual researchers carried out independent work and the group collectively pooled data. RESULTS: Three axes of experience were identified: (i) the loss of meaning, that is being a doctor, no longer has any meaning in the actual context of public hospitals; (ii) "the tower of Babel", the impossibility of dialogue with both management and colleagues; and (iii) physicians' daily interactions: too many conflicts, too much pressure and not enough recognition. CONCLUSION: Physicians in this study described being exposed to a deleterious atmosphere, experiencing both emotional abuse and structural violence within the workplace. They considered that such an environment could contribute to the development of burnout. Further research is necessary to assess this hypothesis.